Biometrics and nutritional status of white oat (Avena sativa L.) culture under Bacillus subtilis and B. megaterium inoculation (Research, Society and Development, 2021)
The aim of this work was to evaluate responses of Avena sativa L. to inoculation, with isolates of Bacillus subtilis and B. megaterium.The experiment was carried out on soil classified as dystrophic Red Latosol in the municipality of Campo Grande, MS. The treatments consisted of five doses of inoculant (0, 50, 100, 150, 200 mL), applied in the planting furrow, being distributed in experimental plots, with the dimensions of 3.0 mx 4.0 m, according to the outline in random blocks with four repetitions. The biometric parameters of the plant were evaluated: tiller diameter and tiller quantity, fresh and dry shoot biomass production, grain production. The quality of the product evaluated the bromatology and the mineral content of the flag leaf. Oat plants showed an increase in growth rate (TC), tiller diameter (DP), leaf contents of N, Fe and Cu, crude protein (PB), neutral detergent fiber (NDF). The performance of oats was favored with doses of inoculant up to 125 mL. It was also observed an increasing of protein concentration in the plant in a concentration-response fashion. It is concluded that the inoculant based on the two isolates of the bacteria used in the planting furrow, benefits the production of oats.